Diagnosis and indications for revascularization in Takayasu's Arteritis: Report of two cases and literature review - Magaye Gaye; Adama Sawadogo; Papa Adama Dieng; Ndèye Fatou Sow; Souleymane Diatta; Momar Sokhna Diop; Papa Salmane Ba; Assane Ndiaye; Amadou Gabriel Ciss; Mouhamadou Ndiaye (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
Takayasu's arteritis (TA) is an inflammatory disease of large vessels that predominantly affects the aorta and its main branches such as supra-aortic trunks, renal and digestive arteries. The diagnosis is based on criteria proposed by the American College of Rheumatology and modifi ed by Sharma. These vascular lesions present a problem of surgical indications because of their pathogenic particularity. In this work, we report our experience on the diagnosis and management of two cases of TA. The case 1 was a 62-year-old female patient diagnosed with stenosis of the common carotid artery and the right subclavian artery. A bypass between the carotid artery and the subclavian artery was indicated but not performed. The second patient was a 23-year-old female patient diagnosed with renovascular hypertension. Investigations showed a significant stenosis of the left renal artery. She underwent angioplasty-stenting of the left renal artery and the result was good. Her echocardiography showed left ventricular and atrial hypertrophy and both. The two patients had no indirect signs of myocardial ischemia and arterial pulmonary injuries